2009
DOI: 10.1080/00365540802468094
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes: Maternal-foetal infections in Denmark 1994–2005

Abstract: Maternal-foetal infection by Listeria monocytogenes is a rare complication in pregnancy. In the period 1994-2005, 37 culture-confirmed cases of maternal-foetal Listeria monocytogenes infections were reported in Denmark. We examined 36 patients' files in order to evaluate risk factors, clinical and laboratory findings, response to therapy, and outcome for maternal-foetal listeriosis. Patient data and bacteriological findings were divided into 2 groups for comparison: 1 group with children born alive (n=24) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 9 publications
3
42
1
2
Order By: Relevance
“…This bacterium can cause miscarriages in pregnant women and meningitis in newborns, children and adults who are immunosuppressed (Donelly, 1994;Posfay-Barbe & Wald, 2004;Seeliger, 1961;Shih-Yu et al, 2007;Smith et al, 2009). L. monocytogenes and Listeria innocua are the most frequently isolated strains in food processing plants.…”
Section: Introductionmentioning
confidence: 97%
“…This bacterium can cause miscarriages in pregnant women and meningitis in newborns, children and adults who are immunosuppressed (Donelly, 1994;Posfay-Barbe & Wald, 2004;Seeliger, 1961;Shih-Yu et al, 2007;Smith et al, 2009). L. monocytogenes and Listeria innocua are the most frequently isolated strains in food processing plants.…”
Section: Introductionmentioning
confidence: 97%
“…L. monocytogenes is widely considered to be one of the leading causes of food-borne infections with high case fatalities (40). Also, infection with L. monocytogenes during pregnancy can lead to choriomeningitis and miscarriage (29,37). Immunity to systemic infections in listeriosis has been linked to cellular immunity and more recently to components of the innate immune response (4).…”
mentioning
confidence: 99%
“…In a recent US study, 16.9% of Listeria cases were associated with pregnancy, 20.3% of which resulted in fetal loss, and 80% of which occurred during the first 24 weeks of pregnancy, 24 whereas a Danish study reported 33.3% fetal loss among pregnant women with L monocytogenes infections. 25 Although unencapsulated H influenzae commonly colonizes the human upper respiratory tract, it can also colonize the female reproductive tract and can cause pelvic inflammatory disease.…”
mentioning
confidence: 99%